A positive electrode sheet and a battery using the same
Patent Information
- Application Number
- CN202611136079.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-09
AI Technical Summary
卷绕过程中,R角处的正极涂层材料受到显著的压缩应力和拉伸应力,当应力超过涂层材料的承受极限时,LFP/石墨等活性材料颗粒发生断裂,导致活性物质脱落、掉粉甚至漏铜
本发明通过“底层高导电高柔韧层”与“顶层原位自修复层”的双层协同设计,有效改善了卷绕电芯R角区域的失效问题,显著提升了电池的循环寿命、倍率性能和安全性。
Smart Images

Figure CN122889692A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a positive electrode sheet and a battery using it. Background Technology
[0002] Rolled lithium-ion batteries are widely used in power batteries and consumer electronics due to their high manufacturing efficiency and good space utilization. However, during the manufacturing process of rolled cells, the bending radius (R angle) area has long faced a series of key problems restricting battery performance and lifespan due to electrode bending deformation and mechanical stress concentration. These are as follows: (1) Coating cracking and active material shedding in the R-corner area. During the winding process, the positive electrode coating material at the R-corner is subjected to significant compressive and tensile stress. When the stress exceeds the coating material's tolerance limit, the active material particles such as LFP / graphite break, leading to active material shedding, powder loss, and even copper leakage. Insufficient electrode flexibility will further aggravate electrode cracking and pulverization during charging and discharging, resulting in poorer contact between the active material and the current collector, increased internal resistance, and accelerated capacity decay. This structural damage not only directly affects battery capacity but may also cause safety hazards such as internal short circuits.
[0003] (2) Current density distortion in the R-corner region. The curvature at the R-corner leads to an extended electron conduction path and a significant increase in local current density (studies suggest it can reach 1.5 to 2 times that of the planar region), exacerbating the uneven deposition of lithium ions in the R-corner region. Uneven current density can also easily lead to polarization, and long-term cycling will further aggravate lithium plating and material failure. When the electrode breaks or the coating peels off, it will disrupt the lithium ion transport path, causing a significant increase in current density in this region, which in turn induces lithium plating.
[0004] (3) Insufficient electrolyte wetting in the R-corner region. In traditional wound structures, the porosity at the R-corner decreases by 30% to 40% due to the tight stacking of the electrodes, severely hindering electrolyte penetration and wetting, forming the so-called "lithium-ion transport dead zone". Insufficient electrolyte wetting directly affects the battery's capacity, rate performance, and cycle life. When the core is too tightly wound, the internal porosity decreases, hindering electrolyte penetration; and when the electrode compaction density is too high, the porosity will also decrease, which is not conducive to electrolyte wetting of the electrodes.
[0005] To address the aforementioned issues, several technical solutions have been proposed. For example, increasing the radius and reducing the curvature at the rounded corners by inserting support members within the core can effectively prevent cracking and material loss during electrode hot pressing; optimizing the winding process by setting the winding tension to a decay function model that decreases layer by layer; improving lithium plating by setting the roller pressure in the rounded area to be lower than that in the non-rounded area; and enhancing electrolyte permeability by drilling through holes in the rounded corners. Furthermore, some solutions reduce the risk of lithium plating by adding protrusions to the negative electrode active material layer in the corner area to increase the lithium intercalation space.
[0006] However, these existing technical solutions mainly focus on adjusting process parameters (such as tension control and roller pressure zoning) or optimizing structural design (such as adding support components and opening through holes). They can alleviate certain problems in the R-corner region to a certain extent, but cannot simultaneously solve the multiple coupled problems faced by the R-corner region, such as mechanical failure, electrochemical inhomogeneity, and insufficient electrolyte wetting. Summary of the Invention
[0007] To address the problems and shortcomings of existing technologies, this invention provides a positive electrode sheet and a battery using the same. The positive electrode sheet provided by this invention, through the design of two specific active material layers working together, effectively improves a series of problems caused by the bending radius (R angle) region in wound battery cells, further enhancing the electrochemical performance of the battery.
[0008] According to a first aspect of the present invention, a positive electrode is provided, comprising a current collector, a first active material layer, and a second active material layer, wherein the first active material layer and the second active material layer are disposed sequentially away from the current collector; the first active material layer comprises a first active material, an elastic conductive polymer, and carbon-coated copper nanoparticles; the second active material layer comprises a second active material and a functional molecule; the functional molecule is an amphiphilic organic-inorganic hybrid molecule with the general formula R1-Spacer-M(OR2). n R1 includes at least one of phosphonic acid group (-PO(OH)2) and alkoxysilane group; Spacer is a flexible organic segment, including -(CH2CH2O). a -、-(CH2) b - at least one of the following, a = 1~6, b = 3~12; M(OR2) n In this context, M includes Al. 3+ Zr 4+ Ti 4+ Si 4+ Ce 4+ Y 3+ Mg 2+ At least one of them, R2 is an alkyl chain, and the alkyl chain has 2 to 4 carbon atoms and n is 2 to 5.
[0009] Preferably, the elastic conductive polymer includes at least one of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite and polystyrene sulfonate; and / or, the carbon-coated copper nanoparticles include at least one of graphene-coated copper nanoparticles and amorphous carbon-coated copper nanoparticles.
[0010] Preferably, the preparation method of the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite includes: oxidative polymerization of EDOT monomer in the presence of an oxidant; mixing the obtained product with PSS to obtain the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite.
[0011] Preferably, the oxidant includes persulfate. Generally, in the presence of an oxidant (such as persulfate), EDOT monomers undergo oxidative polymerization to generate positively charged PEDOT. + The chain, and PSS is negatively charged, therefore, with negatively charged PSS - As a dopant and stabilizer, with PEDOT + Through electrostatic bonding, a PEDOT:PSS complex (i.e., poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate complex) can be formed. In this complex, PSS... - Encased in rigid PEDOT + Stable colloidal nanoparticles are formed around the chain and dispersed in the aqueous solution.
[0012] Preferably, the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite was purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., product model XFJ224.
[0013] Preferably, the preparation method of graphene-coated copper nanoparticles is as follows: (1) The reactor loaded with copper nanoparticles is placed in a chemical vapor deposition device and heated to 600-800°C under inert gas, and hydrogen is introduced for annealing for 2-4 hours; (2) Then carbon source gas is introduced at 800-1000°C and the reaction is carried out for 4-6 hours; (3) The carbon source gas is turned off and the mixture is slowly cooled to room temperature under inert gas protection to obtain graphene-coated copper nanoparticles.
[0014] Preferably, in the above method for preparing graphene-coated copper nanoparticles, in step (1), the chemical vapor deposition equipment is a CVD furnace; and / or, in steps (1) and (3), the inert gas includes at least one of nitrogen and argon; and / or, in step (2), the carbon source gas includes at least one of methane, ethylene, and acetylene.
[0015] Preferably, the preparation method of amorphous carbon-coated copper nanoparticles differs from the preparation method of graphene-coated copper nanoparticles in that, in step (2), carbon source gas is introduced at 500-700℃; the rest of the operations are the same.
[0016] Preferably, the functional molecule includes at least one of (HO)2OP-(CH2)3-O-Al(OC2H5)2 and (EtO)3Si-(CH2)3-O-Zr(OEt)3.
[0017] Preferably, the preparation of (HO)2OP-(CH2)3-O-Al(OC2H5)2 is as follows: (3-chloropropyl)phosphonic acid is dissolved in anhydrous ethanol in an argon glove box; an ethanol solution of aluminum ethoxide is slowly added dropwise under ice bath and stirring; the mixture is gradually restored to room temperature and stirred for 12-24 hours; after the reaction is completed, the solvent ethanol and the byproduct ethane chloride are removed by vacuum distillation to obtain a viscous pale yellow liquid or solid, which is the target product.
[0018] Preferably, the preparation of (EtO)3Si-(CH2)3-O-Zr(OEt)3 is as follows: In an argon glove box, 3-chloropropyltriethoxysilane and anhydrous triethylamine catalyst are dissolved in anhydrous n-propanol; under ice bath and stirring, an anhydrous n-propanol solution of tetra-n-propoxyzirconium is slowly added dropwise; the temperature is gradually raised to 60-80°C, and the reaction is continued to be stirred for 12-24 hours; after the reaction is completed, the generated triethylamine hydrochloride white solid is removed by filtration, and the filtrate is subjected to vacuum distillation to remove the solvent n-propanol and excess triethylamine, and then the target product is obtained by vacuum distillation. The product is a colorless to pale yellow viscous liquid.
[0019] Preferably, based on the total mass of the first active material layer, the content of the first active material is 60-70%, the content of the elastic conductive polymer is 22-32%, and the content of carbon-coated copper nanoparticles is 3-8%; and / or, based on the total mass of the second active material layer, the content of the second active material is 92-98%, and the content of functional molecules is 0.5-4%.
[0020] More preferably, based on the total mass of the first active material layer, the content of the first active material is 65-66%, the content of the elastic conductive polymer is 26-28%, and the content of carbon-coated copper nanoparticles is 5-6%; and / or, based on the total mass of the second active material layer, the content of the second active material is 94-95%, and the content of functional molecules is 1-2%.
[0021] Preferably, the compaction density of the positive electrode sheet is 2.5-2.8 g / cm³. 3 And / or, the thickness ratio of the first active material layer to the second active material layer is 1~2:1~2. More preferably, the compaction density of the positive electrode sheet is 2.62-2.65 g / cm³.3 .
[0022] Preferably, the thickness of the first active material layer is 80-180 μm; and / or, the thickness of the second active material layer is 80-180 μm.
[0023] Preferably, the thickness of the current collector is in the range of 12-15 μm. Preferably, the current collector is aluminum foil.
[0024] Preferably, in the first active material layer, the first active material includes at least one of lithium iron phosphate cathode material (LFP), ternary nickel cobalt manganese cathode material (NCM), and lithium manganese iron phosphate cathode material (LFMP); and / or, in the second active material layer, the second active material includes at least one of lithium iron phosphate cathode material, ternary nickel cobalt manganese cathode material, and lithium manganese iron phosphate cathode material.
[0025] Preferably, the first active material layer further includes a first dispersant and a first binder; based on the total mass of the first active material layer, the content of the first dispersant is 0.5~0.6%, and the content of the first binder is 0.4~2.5%; and / or, the second active material layer further includes a second dispersant, a second binder, and a conductive agent; based on the total mass of the second active material layer, the content of the second dispersant is 0.2~0.3%, the content of the second binder is 0.7~3.3%, and the content of the conductive agent is 1.5-2%.
[0026] Preferably, the first dispersant comprises at least one of polypropylene glycol phosphate, sodium dodecyl sulfate (SDS), polyethylene glycol (PEG), sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, polyacrylonitrile (LPAN), and polyvinylpyrrolidone; the first binder comprises polyvinylidene fluoride (PVDF); and / or, the second dispersant comprises at least one of polypropylene glycol phosphate, sodium dodecyl sulfate, polyethylene glycol (PEG), sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, polyacrylonitrile, and polyvinylpyrrolidone; the second binder comprises polyvinylidene fluoride; and the conductive agent comprises at least one of conductive carbon black, Ketjen black, carbon nanotubes, and graphene.
[0027] Preferably, the method for preparing the positive electrode sheet includes the following steps: S1, preparing a first positive electrode slurry using a first active material, an elastic conductive polymer, carbon-coated copper nanoparticles, a first dispersant, and a first binder; preparing a second positive electrode slurry using a second active material, a functional molecule, a second dispersant, a second binder, and a conductive agent; S2, sequentially coating the first positive electrode slurry and the second positive electrode slurry onto a current collector, drying, and compacting to obtain the positive electrode sheet.
[0028] Preferably, in S1, the solvent used in preparing the first positive electrode slurry and the second positive electrode slurry includes water.
[0029] Preferably, in S1, the second active material and functional molecule need to be pretreated before the second positive electrode slurry is prepared. The specific operation of the pretreatment is as follows: the functional molecule is dissolved in an alcohol solvent to obtain a first solution; then the second active material is added to the first solution and reacted at 60-70°C for 4-6 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried.
[0030] Preferably, the alcohol solvent includes ethanol.
[0031] Preferably, in step S2, the drying temperature is 80~100℃.
[0032] According to a second aspect of the present invention, a battery is provided, comprising the positive electrode sheet described in any of the preceding claims.
[0033] Compared with the prior art, the present invention has the following technical effects: This invention effectively improves the failure problem in the R-corner area of the wound cell by using a dual-layer synergistic design of a "bottom high conductivity and high flexibility layer" and a "top in-situ self-healing layer", which significantly improves the cycle life, rate performance and safety of the battery.
[0034] Specifically, in the first active material layer (bottom layer), the low Young's modulus of the elastic conductive polymer significantly reduces the bending stress of the electrode, alleviating coating cracking and active material detachment caused by bending stress in the R-corner region of the wound cell. Simultaneously, the high conductivity of carbon-coated copper nanoparticles is used to construct a three-dimensional conductive network, ensuring uniform current distribution and suppressing uneven lithium-ion deposition and lithium plating caused by excessively high local current density in the R-corner region. In the second active material layer (top layer), the amphiphilic organic-inorganic hybrid functional molecule R1-Spacer-M(OR2) is introduced. n It utilizes the strong affinity of its R1 end group for transition metal ions exposed on the fresh fracture surface of the cathode material to achieve automatic crack identification and anchoring, and utilizes its M(OR2) n The end groups hydrolyze, fluorinate, and condense in the crack microenvironment, forming an in-situ metal fluoride oxide composite inorganic network that "welds" and seals the crack, preventing crack propagation and further electrolyte erosion, while consuming harmful HF and passivating fresh interfaces. Attached Figure Description
[0035] Figure 1 This is a schematic diagram of the structure of one of the positive electrode sheets of the present invention; wherein, 1-current collector, 2-first active material layer, 3-second active material layer.
[0036] Figure 2 This is an electron microscope (SEM) image of the negative electrode (R-corner) after the battery in Example 3 of this invention has been disassembled after 1000 cycles. Note: The SEM image shows the R-corner position of the negative electrode corresponding to the positive electrode (lithium plating generally occurs on the negative electrode side, and the positive electrode cannot reach the lithium plating potential).
[0037] Figure 3 This is an electron microscope (SEM) image of the negative electrode (at the R-corner) after the battery in Comparative Example 1 of this invention has been disassembled after 1000 cycles. Note: The SEM image shows the R-corner position of the negative electrode corresponding to the positive electrode. Detailed Implementation
[0038] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0039] According to a first aspect of the present invention, a positive electrode is provided, comprising a current collector, a first active material layer, and a second active material layer, wherein the first active material layer and the second active material layer are disposed sequentially away from the current collector; the first active material layer comprises a first active material, an elastic conductive polymer, and carbon-coated copper nanoparticles; the second active material layer comprises a second active material and a functional molecule; the functional molecule is an amphiphilic organic-inorganic hybrid molecule with the general formula R1-Spacer-M(OR2). n R1 includes at least one of phosphonic acid group (-PO(OH)2) and alkoxysilane group; Spacer is a flexible organic segment, including -(CH2CH2O). a -、-(CH2) b - at least one of the following, a = 1~6, b = 3~12; M(OR2) n In this context, M includes Al. 3+ Zr 4+ Ti 4+ Si 4+ Ce 4+ Y 3+ Mg 2+ At least one of them, R2 is an alkyl chain, and the alkyl chain has 2 to 4 carbon atoms and n is 2 to 5.
[0040] The positive electrode sheet provided by this invention introduces two active material layers with specific functions, which effectively improves a series of problems caused by the bending radius (R angle) region in the wound cell, and can significantly improve the battery's cycle performance and other electrochemical performance.
[0041] Specifically, firstly, in the first active material layer near the current collector, an elastic conductive polymer and carbon-coated copper particles are introduced. The elastic conductive polymer has a low Young's modulus, which can effectively reduce the overall bending stress of the electrode. That is, when the wound cell bends and deforms in the R-corner region, the elastic conductive polymer can absorb and buffer the mechanical stress generated by compression and tension inside the coating, significantly alleviating the problems of active material particle breakage, coating peeling or delamination caused by stress concentration at the corner, thereby improving the structural integrity and processing yield of the electrode. Meanwhile, the carbon-coated copper nanoparticles can construct a highly efficient three-dimensional conductive network in the first active material layer, which can significantly reduce the electron transport impedance of the electrode, ensure the uniform distribution of current density in the bending state of the R-corner region, and effectively suppress the uneven deposition and lithium plating of lithium ions induced by excessive local current. Therefore, the elastic conductive polymer and carbon-coated copper particles together endow the first active material layer (bottom layer) with both "high conductivity" and "high flexibility", which can effectively solve the problems of current distortion and mechanical failure in the R-corner region.
[0042] Secondly, a second active material layer (top layer) above the first active material layer is introduced, with the general formula R1-Spacer-M(OR2). n This is an amphiphilic organic-inorganic hybrid functional molecule. Through its R1 end group (phosphonic acid group or siloxy group), this molecule exhibits a strong chemical affinity for transition metal ions exposed on the surface of the positive electrode active material. Therefore, when microcracks form on the electrode during R-angle bending or long-term cycling, exposing transition metal ions at the fresh fracture surface, this functional molecule can preferentially anchor to the inner surface of the crack via its R1 end group, achieving automatic crack recognition and targeted localization. Furthermore, the M(OR2) of this functional molecule... n When the end group encounters trace amounts of moisture within the contact crack and HF generated from the hydrolysis of LiPF6 in the electrolyte, it undergoes rapid hydrolysis, fluorination, and condensation reactions, forming an in-situ ternary composite inorganic network with metal fluoride as the main component. This inorganic network firmly "welds" the interfaces on both sides of the crack, effectively sealing the crack path, preventing further crack propagation, and blocking the electrolyte from eroding inward along the crack. Therefore, it can effectively repair surface cracks on the electrode and significantly extend the cycle life of the battery. Furthermore, the metal fluoride has a fluorine-rich surface structure, which can efficiently passivate the fresh active surface at the crack and suppress interfacial side reactions. At the same time, this repair process can consume corrosive HF in the electrolyte in situ, slowing down the metal dissolution and structural degradation of the cathode material, further improving the stability of the battery under high temperature and high voltage.
[0043] In summary, this invention effectively improves the failure problem in the radius (R) corner region of wound battery cells through a dual-layer synergistic design of a "bottom layer with high conductivity and high flexibility (first active material layer)" and a "top layer with in-situ self-healing properties (second active material layer)." Specifically, the bottom layer reduces bending stress and current density distortion, preventing crack formation; the top layer rapidly initiates in-situ repair once a crack occurs, preventing crack propagation and electrolyte erosion. The two layers work together to significantly improve the structural stability, electrochemical uniformity, and interface durability of the radius (R) corner region of the wound battery cell, reduce the risk of lithium plating, and enhance the battery's rate performance, cycle life, and safety performance.
[0044] Preferably, the elastic conductive polymer includes at least one of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite and polystyrene sulfonate; and / or, the carbon-coated copper nanoparticles include at least one of graphene-coated copper nanoparticles and amorphous carbon-coated copper nanoparticles.
[0045] The poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite possesses both electronic and ionic conductivity. The flexibility of its PSS segments endows the polymer with a low Young's modulus, which can effectively buffer the bending stress at the radius of curvature. Furthermore, within the aforementioned mass ratio range, it can ensure the synergistic balance between the PEDOT conductive network and the PSS flexible skeleton, maximizing stress buffering capacity while ensuring high conductivity of the underlying layer, and effectively suppressing coating cracking and material loss.
[0046] The carbon coating layers involved in the aforementioned carbon-coated copper nanoparticles can prevent the copper core from oxidizing and agglomerating, ensuring the dispersion stability and long-term conductivity reliability of the nanoparticles in the slurry.
[0047] Preferably, the preparation method of the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite includes: oxidative polymerization of EDOT monomer in the presence of an oxidant; mixing the obtained product with PSS to obtain the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite.
[0048] Preferably, the oxidant includes persulfate. Generally, in the presence of an oxidant (such as persulfate), EDOT monomers undergo oxidative polymerization to generate positively charged PEDOT. + The chain, and PSS is negatively charged, therefore, with negatively charged PSS - As a dopant and stabilizer, with PEDOT + Through electrostatic bonding, a PEDOT:PSS complex (i.e., poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate complex) can be formed. In this complex, PSS... - Encased in rigid PEDOT + Stable colloidal nanoparticles are formed around the chain and dispersed in the aqueous solution.
[0049] Preferably, the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite was purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., product model XFJ224.
[0050] Preferably, the preparation method of graphene-coated copper nanoparticles is as follows: (1) The reactor loaded with copper nanoparticles is placed in a chemical vapor deposition device and heated to 600-800°C under inert gas, and hydrogen is introduced for annealing for 2-4 hours; (2) Then carbon source gas is introduced at 800-1000°C and the reaction is carried out for 4-6 hours; (3) The carbon source gas is turned off and the mixture is slowly cooled to room temperature under inert gas protection to obtain graphene-coated copper nanoparticles.
[0051] In step (1), the purpose of annealing with hydrogen gas is to remove the oxide layer on the copper surface and obtain a pure copper surface with catalytic activity. In step (2), a carbon source gas is introduced for reaction, and the carbon source gas decomposes on the copper surface to form a continuous graphene film coating the surface of the copper nanoparticles. In step (3), slow cooling to room temperature under inert gas protection helps to form a complete and ordered graphene lattice.
[0052] Preferably, in the above method for preparing graphene-coated copper nanoparticles, in step (1), the chemical vapor deposition equipment is a CVD furnace; and / or, in steps (1) and (3), the inert gas includes at least one of nitrogen and argon; and / or, in step (2), the carbon source gas includes at least one of methane, ethylene, and acetylene.
[0053] Preferably, the preparation method of amorphous carbon-coated copper nanoparticles differs from the preparation method of graphene-coated copper nanoparticles in that, in step (2), carbon source gas is introduced at 500-700℃; the rest of the operations are the same.
[0054] Preferably, the functional molecule includes at least one of (HO)2OP-(CH2)3-O-Al(OC2H5)2 and (EtO)3Si-(CH2)3-O-Zr(OEt)3. Using the above functional molecules ensures that they quickly anchor at the crack site and form a metal fluoride repair network in situ, effectively sealing the crack, passivating the fresh interface, and consuming harmful HF, significantly improving repair efficiency and durability. Therefore, it can effectively improve the battery's cycle performance and rate performance.
[0055] Preferably, the preparation of (HO)2OP-(CH2)3-O-Al(OC2H5)2 is as follows: (3-chloropropyl)phosphonic acid is dissolved in anhydrous ethanol in an argon glove box; an ethanol solution of aluminum ethoxide is slowly added dropwise under ice bath and stirring; the mixture is gradually restored to room temperature and stirred for 12-24 hours; after the reaction is completed, the solvent ethanol and the byproduct ethane chloride are removed by vacuum distillation to obtain a viscous pale yellow liquid or solid, which is the target product.
[0056] Preferably, the preparation of (EtO)3Si-(CH2)3-O-Zr(OEt)3 is as follows: In an argon glove box, 3-chloropropyltriethoxysilane and anhydrous triethylamine catalyst are dissolved in anhydrous n-propanol; under ice bath and stirring, an anhydrous n-propanol solution of tetra-n-propoxyzirconium is slowly added dropwise; the temperature is gradually raised to 60-80°C, and the reaction is continued to be stirred for 12-24 hours; after the reaction is completed, the generated triethylamine hydrochloride white solid is removed by filtration, and the filtrate is subjected to vacuum distillation to remove the solvent n-propanol and excess triethylamine, and then the target product is obtained by vacuum distillation. The product is a colorless to pale yellow viscous liquid.
[0057] Preferably, based on the total mass of the first active material layer, the content of the first active material is 60-70%, the content of the elastic conductive polymer is 22-32%, and the content of carbon-coated copper nanoparticles is 3-8%; and / or, based on the total mass of the second active material layer, the content of the second active material is 92-98%, and the content of functional molecules is 0.5-4%.
[0058] In the first active material layer, 60-70% active material ensures high energy density, while 22-32% elastic conductive polymer within this content range is sufficient to form a continuous, flexible conductive network. 3-8% carbon-coated copper nanoparticles ensure uniform dispersion within the polymer network, constructing a stable three-dimensional conductive framework and effectively reducing contact resistance. Within the aforementioned content range, these three components synergistically balance various performance aspects, ensuring both the efficiency of the underlying electron transport and maximizing stress relief, effectively suppressing coating cracking in the R-corner region and uneven lithium deposition.
[0059] In the second active material layer, 92-98% of the active material ensures high areal capacity and energy density in the top layer, meeting the overall performance requirements of the battery. 0.5-4% of functional molecules, added in extremely low amounts, achieves uniform molecular-level chemical anchoring on the surface of the active material particles. This content range ensures sufficient functional molecules for migration and reaction on the inner surface when cracks occur, forming a continuous and complete inorganic repair network, while avoiding the problems of functional molecule self-condensation, blockage of lithium-ion insertion / extraction channels on the active material surface, or increased interfacial impedance caused by excessive addition. At a content of 1-2%, functional molecules can efficiently perform crack recognition and in-situ repair functions without sacrificing the electrochemical performance of the top layer, achieving a balance between "high capacity retention" and "crack self-repair."
[0060] More preferably, based on the total mass of the first active material layer, the content of the first active material is 65-66%, the content of the elastic conductive polymer is 26-28%, and the content of carbon-coated copper nanoparticles is 5-6%; and / or, based on the total mass of the second active material layer, the content of the second active material is 94-95%, and the content of functional molecules is 1-2%.
[0061] Preferably, the compaction density of the positive electrode sheet is 2.5-2.8 g / cm³. 3 ; and / or, the thickness ratio of the first active material layer to the second active material layer is 1~2:1~2.
[0062] The compaction range of the above-mentioned positive electrode can balance high energy density and suitable porosity, ensuring sufficient contact between active particles to reduce internal resistance, while retaining electrolyte wetting channels, so that the R-corner region has good electronic conduction and ion transport performance, avoiding lithium plating.
[0063] The thickness ratio of the first and second active material layers is controlled within the above range. On the one hand, this ensures that the bottom layer has sufficient thickness to bear the functions of stress buffering and current equalization. On the other hand, it ensures that the top layer has an appropriate thickness to guarantee continuous coverage and rapid response of the self-healing layer, thereby achieving the optimal synergy between the flexible protection of the bottom layer and the interface repair of the top layer.
[0064] Preferably, the compaction density of the positive electrode sheet is 2.62-2.65 g / cm³. 3 .
[0065] Preferably, the thickness of the first active material layer is 80-180 μm; and / or, the thickness of the second active material layer is 80-180 μm.
[0066] Preferably, the thickness of the current collector is in the range of 12-15 μm. Preferably, the current collector is aluminum foil.
[0067] Preferably, in the first active material layer, the first active material includes at least one of lithium iron phosphate cathode material (LFP), ternary nickel cobalt manganese cathode material (NCM), and lithium manganese iron phosphate cathode material (LFMP); and / or, in the second active material layer, the second active material includes at least one of lithium iron phosphate cathode material, ternary nickel cobalt manganese cathode material, and lithium manganese iron phosphate cathode material.
[0068] Preferably, the first active material layer further includes a first dispersant and a first binder; based on the total mass of the first active material layer, the content of the first dispersant is 0.5~0.6%, and the content of the first binder is 0.4~2.5%; and / or, the second active material layer further includes a second dispersant, a second binder, and a conductive agent; based on the total mass of the second active material layer, the content of the second dispersant is 0.2~0.3%, the content of the second binder is 0.7~3.3%, and the content of the conductive agent is 1.5-2%.
[0069] Preferably, the first dispersant comprises at least one of polypropylene glycol phosphate, sodium dodecyl sulfate (SDS), polyethylene glycol (PEG), sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, polyacrylonitrile (LPAN), and polyvinylpyrrolidone; the first binder comprises polyvinylidene fluoride (PVDF); and / or, the second dispersant comprises at least one of polypropylene glycol phosphate, sodium dodecyl sulfate, polyethylene glycol (PEG), sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, polyacrylonitrile, and polyvinylpyrrolidone; the second binder comprises polyvinylidene fluoride; and the conductive agent comprises at least one of conductive carbon black, Ketjen black, carbon nanotubes, and graphene. Preferably, the method for preparing the positive electrode sheet includes the following steps: S1, preparing a first positive electrode slurry using a first active material, an elastic conductive polymer, carbon-coated copper nanoparticles, a first dispersant, and a first binder; preparing a second positive electrode slurry using a second active material, a functional molecule, a second dispersant, a second binder, and a conductive agent; S2, sequentially coating the first positive electrode slurry and the second positive electrode slurry onto a current collector, drying, and compacting to obtain the positive electrode sheet.
[0070] Preferably, in S1, the solvent used in preparing the first positive electrode slurry and the second positive electrode slurry includes water.
[0071] Preferably, in step S1, the second active material and functional molecules need to be pretreated before the second positive electrode slurry is prepared. The specific pretreatment operation is as follows: the functional molecules are dissolved in an alcohol solvent to obtain a first solution; then the second active material is added to the first solution, and the reaction is carried out at 60-70°C for 4-6 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried. The above pretreatment operation enables the functional molecules to be firmly anchored to the entire surface of the second active material particles through chemical bonding.
[0072] Preferably, the alcohol solvent includes ethanol.
[0073] Preferably, in step S2, the drying temperature is 80~100℃.
[0074] According to a second aspect of the present invention, a battery is provided, comprising the positive electrode sheet described in any of the preceding claims. The battery comprising the aforementioned positive electrode sheet synergistically improves the problems of coating cracking, uneven lithium deposition, and insufficient electrolyte wetting in the R-corner region of the wound cell, significantly extending cycle life and enhancing rate performance and safety.
[0075] To further illustrate the present invention, the following embodiments will be described in detail.
[0076] Example 1 1. Preparation of positive electrode sheet Preparation of the first positive electrode slurry: LFP, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite (Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., product model XFJ224), graphene-coated copper nanoparticles, polypropylene glycol phosphate (dispersant), and PVDF (binder) were mixed and stirred in an appropriate amount of NMP at a mass ratio of 65:28:5:0.5:1.5 to obtain the first positive electrode slurry.
[0077] The preparation method of graphene-coated copper nanoparticles includes the following steps: (1) The reactor loaded with copper nanoparticles was placed in a CVD furnace, heated to 600°C under argon, and annealed for 2 hours by introducing hydrogen. (2) Then, carbon source (methane) gas was introduced at 1000℃ and the reaction was carried out for 6 hours; (3) After the reaction is complete, the carbon source gas is turned off and the mixture is slowly cooled to room temperature under argon protection to obtain graphene-coated copper nanoparticles.
[0078] Preparation of the second positive electrode slurry: (HO)2OP-(CH2)3-O-Al(OC2H5)2 (functional molecule) was dissolved in anhydrous ethanol, and then LFP powder was added (the mass ratio of LFP to (HO)2OP-(CH2)3-O-Al(OC2H5)2 was 94.5:1.5). The mixture was stirred at 60°C for 6 hours. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain a solid powder. The solid powder was then mixed with conductive carbon black, polypropylene glycol phosphate, and PVDF (the amounts of conductive carbon black, polypropylene glycol phosphate, and PVDF were calculated based on the mass ratio of LFP to (HO)2OP-(CH2)3-O-Al(OC2H5)2, conductive carbon black, polypropylene glycol phosphate, and PVDF being 94.5:1.5:1.5:0.2:2.3) in an appropriate amount of NMP to obtain the second positive electrode slurry.
[0079] The preparation method of (HO)2OP-(CH2)3-O-Al(OC2H5)2 includes the following steps: (3-chloropropyl)phosphonic acid is dissolved in anhydrous ethanol in an argon glove box; an ethanol solution of aluminum ethoxide is slowly added dropwise under ice bath and stirring; the mixture is gradually restored to room temperature and stirred for 18 hours; after the reaction is completed, the solvent ethanol and the byproduct ethane chloride are removed by vacuum distillation to obtain a viscous pale yellow liquid or solid, which is the target product.
[0080] Preparation of the positive electrode sheet: A multi-die slit coater was used to sequentially and uniformly coat the first positive electrode slurry (corresponding to the first positive electrode active coating) and the second positive electrode slurry (corresponding to the second positive electrode active coating) onto an Al foil (coating both sides of the Al foil), with a coating weight ratio of 1:1 between the upper and lower layers. The oven temperature was set to 100℃ for drying, followed by rolling to obtain the positive electrode sheet. The Al foil thickness was 14 μm, the first active material layer thickness was 37 μm, and the second active material layer thickness was 37 μm, i.e., the thickness ratio of the first active material layer to the second active material layer was 1:1. The compaction density of the positive electrode sheet was 2.6 g / cm³. 3 .
[0081] 2. Preparation of negative electrode and battery fabrication Preparation of the negative electrode: Graphite, conductive carbon black, CMC, and SBR were added to a certain amount of water in a mass ratio of 96:1.4:1.6:1, and stirred continuously to form a uniform slurry. The slurry was coated onto Cu foil using a coating machine and dried in an oven at 100℃. The dried electrode was then rolled to obtain the negative electrode. The negative electrode had a Cu foil thickness of 8 μm, a negative active material layer thickness of 147 μm, and a compaction density of 1.55 g / cm³. 3 .
[0082] Battery fabrication: The prepared positive and negative electrode sheets and separator are used to fabricate a battery. 1M LiPF6 is dissolved in a mixed solution of EC and DMC (volume ratio of 1:1) as the electrolyte.
[0083] Example 2 1. Preparation of positive electrode sheet The preparation of the first and second positive electrode slurries in this embodiment is the same as in Example 1. The difference from Example 1 lies in the coating weight ratio of the upper and lower layers during the coating process of the first and second positive electrode slurries; the remaining operations are the same as in Example 1. The final thickness of the first active material layer is 50 μm, and the thickness of the second active material layer is 25 μm, i.e., the thickness ratio of the first active material layer to the second active material layer is 2:1; the compaction density of the positive electrode sheet is 2.6 g / cm³. 3 .
[0084] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0085] Example 3 1. Preparation of positive electrode sheet The preparation of the first and second positive electrode slurries in this embodiment is the same as in Example 1. The difference from Example 1 lies in the coating weight ratio of the upper and lower layers during the coating process of the first and second positive electrode slurries; the remaining operations are the same as in Example 1. The final thickness of the first active material layer is 25 μm, and the thickness of the second active material layer is 50 μm, i.e., the thickness ratio of the first active material layer to the second active material layer is 1:2; the compaction density of the positive electrode sheet is 2.6 g / cm³. 3 .
[0086] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0087] Example 4 1. Preparation of positive electrode sheet The preparation of the first positive electrode slurry in this embodiment is the same as in Example 1. The difference between the preparation of the second positive electrode slurry and Example 1 is that the functional molecule is adjusted to (EtO)3Si-(CH2)3-O-Zr(OEt)3, and the rest of the operation is the same as in Example 1.
[0088] The preparation method of (EtO)3Si-(CH2)3-O-Zr(OEt)3 includes the following steps: In an argon glove box, 3-chloropropyltriethoxysilane and anhydrous triethylamine catalyst are dissolved in anhydrous n-propanol; under ice bath and stirring, an anhydrous n-propanol solution of tetra-n-propoxyzirconium is slowly added dropwise; the temperature is gradually raised to 80°C, and the reaction is continued to be stirred for 18 hours; after the reaction is completed, the generated triethylamine hydrochloride white solid is removed by filtration, and the filtrate is subjected to vacuum distillation to first remove the solvent n-propanol and excess triethylamine, and then the target product is distilled off under a higher vacuum. The product is a colorless to pale yellow viscous liquid.
[0089] The preparation of the positive electrode in this embodiment is the same as in Example 1.
[0090] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0091] Example 5 1. Preparation of positive electrode sheet The difference between this embodiment and Embodiment 1 in the preparation of the first positive electrode slurry is that the graphene-coated copper nanoparticles are changed to amorphous carbon-coated copper nanoparticles; the remaining operations are the same as in Embodiment 1. The preparation method of the amorphous carbon-coated copper nanoparticles includes the following steps: (1) The reactor loaded with copper nanoparticles was placed in a CVD furnace, heated to 600°C under argon, and annealed for 2 hours by introducing hydrogen. (2) Then, carbon source (methane) gas was introduced at 600°C and the reaction was carried out for 6 hours; (3) After the reaction is complete, the carbon source gas is turned off and the mixture is slowly cooled to room temperature under argon protection to obtain graphene-coated copper nanoparticles.
[0092] The preparation of the second positive electrode slurry and the positive electrode sheet is the same as in Example 1.
[0093] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0094] Example 6 1. Preparation of positive electrode sheet In the preparation of the first positive electrode slurry in this embodiment, the difference from that in Example 1 is that the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite is adjusted to polystyrene sulfonate (PSS) (HEROCHEM (Shanghai Zhouyuan / Xirun Chemical) PSS (HC0701A)); the rest of the operation is the same as in Example 1.
[0095] The preparation of the second positive electrode slurry and the positive electrode sheet is the same as in Example 1.
[0096] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0097] Example 7 1. Preparation of positive electrode sheet In the preparation of the first positive electrode slurry in this embodiment, the difference from that in Example 1 is that the mass ratio of LFP, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite, graphene-coated copper nanoparticles, polypropylene glycol phosphate, and PVDF is controlled to be 60:32:6:0.5:1.5; the rest of the operation is the same as in Example 1.
[0098] The preparation of the second positive electrode slurry and the positive electrode sheet is the same as in Example 1.
[0099] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0100] Example 8 1. Preparation of positive electrode sheet In the preparation of the first positive electrode slurry in this embodiment, the difference from that in Example 1 is that the mass ratio of LFP, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate composite, graphene-coated copper nanoparticles, polypropylene glycol phosphate, and PVDF is controlled to be 70:22:6:0.5:1.5; the rest of the operation is the same as in Example 1.
[0101] The preparation of the second positive electrode slurry and the positive electrode sheet is the same as in Example 1.
[0102] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0103] Example 9 1. Preparation of positive electrode sheet The preparation of the first positive electrode slurry in this embodiment is the same as in Example 1.
[0104] The second positive electrode slurry preparation process differs from Example 1 in that the mass ratio of LFP, (HO)2OP-(CH2)3-O-Al(OC2H5)2, conductive carbon black, polypropylene glycol phosphate, and PVDF is controlled at 95.5:0.5:1.5:0.2:2.3; the remaining operations are the same as in Example 1.
[0105] The preparation of the positive electrode sheet is the same as in Example 1.
[0106] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0107] Example 10 1. Preparation of positive electrode sheet The preparation of the first positive electrode slurry in this embodiment is the same as in Example 1.
[0108] The second positive electrode slurry preparation process differs from Example 1 in that the mass ratio of LFP, (HO)2OP-(CH2)3-O-Al(OC2H5)2, conductive carbon black, polypropylene glycol phosphate, and PVDF is controlled at 92:4:1.5:0.2:2.3; the remaining operations are the same as in Example 1.
[0109] The preparation of the positive electrode sheet is the same as in Example 1.
[0110] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0111] Comparative Example 1 1. Preparation of positive electrode sheet This comparative example demonstrates the preparation of a conventional lithium iron phosphate (LFP) monolayer active material layer cathode sheet, specifically as follows: LFP, polypropylene glycol phosphate (PPP), PVDF, and conductive agent SP were mixed and stirred in an appropriate amount of NMP at a mass ratio of 96:0.2:1.8:2 to obtain a cathode slurry. The slurry was then uniformly coated onto an Al foil using a coating machine. The oven temperature was set to 100℃, and the sheet was dried and rolled to obtain the cathode sheet. The Al foil thickness was 14 μm, the active material layer thickness was 74 μm, and the compaction density of the cathode sheet was 2.6 g / cm³. 3 .
[0112] Comparative Example 2 1. Preparation of positive electrode sheet The difference between this comparative example and Example 1 in the preparation of the first positive electrode slurry is that no elastic conductive polymer is added (i.e., no poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate complex is included). The formula of the effective material is as follows: LFP, graphene-coated copper nanoparticles, polypropylene glycol phosphate, and PVDF in a mass ratio of 93:5:0.2:1.8; the rest of the operation is the same as in Example 1.
[0113] The preparation of the second positive electrode slurry and the positive electrode sheet is the same as in Example 1.
[0114] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0115] Comparative Example 3 1. Preparation of positive electrode sheet The difference between the preparation of the first positive electrode slurry in this comparative example and Example 1 is that graphene-coated copper nanoparticles are not added. The formula of the effective material is as follows: LFP, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate complex, polypropylene glycol phosphate, and PVDF in a mass ratio of 65:33:0.5:1.5; the rest of the operation is the same as in Example 1.
[0116] The preparation of the second positive electrode slurry and the positive electrode sheet is the same as in Example 1.
[0117] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0118] Comparative Example 4 1. Preparation of positive electrode sheet The preparation of the first positive electrode slurry in this comparative example is the same as that in Example 1.
[0119] The preparation process of the second positive electrode slurry differs from that of Example 1 in that no functional molecules are added (i.e., no (HO)2OP-(CH2)3-O-Al(OC2H5)2 is added). The formula of the effective material is as follows: the mass ratio of LFP, conductive carbon black, polypropylene glycol phosphate and PVDF is 96:2:0.2:1.8; the rest of the operation is the same as that of Example 1.
[0120] The preparation of the positive electrode sheet is the same as in Example 1.
[0121] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0122] Comparative Example 5 1. Preparation of positive electrode sheet The difference between this comparative example and Example 1 is that a first positive electrode slurry is not prepared, and the active material layer is prepared directly using a second positive electrode slurry. The Al foil thickness is 14 μm, and the active material layer thickness is 74 μm; the compaction density of the positive electrode sheet is 2.6 g / cm³. 3 The preparation of the second positive electrode slurry is the same as in Example 1.
[0123] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0124] Comparative Example 6 1. Preparation of positive electrode sheet The difference between this comparative example and Example 1 is that a second positive electrode slurry is not prepared, and the active material layer is prepared directly using the first positive electrode slurry. The Al foil thickness is 14 μm, and the active material layer thickness is 74 μm; the compaction density of the positive electrode sheet is 2.6 g / cm³. 3 The preparation of the first positive electrode slurry is the same as in Example 1.
[0125] 2. Preparation of negative electrode and battery fabrication Consistent with Example 1.
[0126] Test case 1. Experimental Construction Method The batteries prepared in the above embodiments and comparative examples were tested for the following performance: (1) 3C discharge capacity retention rate: The battery was left to stand at 25℃ for 1 hour, then discharged at a constant current of 0.33C to 2.5V, left to stand for 30 minutes, then charged at a constant current of 0.33C to 3.65V, then charged at a constant voltage of 3.65V until the current was less than or equal to 0.05C, left to stand for 30 minutes, then discharged at a constant current of 0.33C to 2.5V, then discharged at a constant voltage of 2.5V until the current was 0.05C. The discharge capacity at this point was recorded as C0 (Ah). After standing for 30 minutes, the battery was charged at a constant current of 0.33C0 (A) to 3.65V, then charged at a constant voltage of 3.65V until the current was less than or equal to 0.05C, then discharged at a constant current of 3C to 2.5V, then discharged at a constant voltage of 2.5V until the current was 0.05C. The discharge capacity at this point was recorded as C1 (Ah). 3C capacity retention rate = C1 / C0 * 100%.
[0127] (2) Capacity retention rate after 1000 cycles: The battery was left to stand at 25°C for 1 hour, then discharged at a constant current of 0.33C to 2.5V, left to stand for 30 minutes, then charged at a constant current of 0.5C to 3.65V, then charged at a constant voltage of 3.65V until the current was less than or equal to 0.05C, left to stand for 30 minutes, then discharged at a constant current of 0.5C to 2.5V, then discharged at a constant voltage of 2.5V until the current was 0.05C. The discharge capacity at this point was recorded as the discharge capacity of the first cycle. After standing for 30 minutes, the capacity of the lithium-ion battery was recorded when the cycle reached 1000 cycles. Capacity retention rate at 1000th cycle = Discharge capacity at 1000th cycle / Discharge capacity at 1st cycle × 100%.
[0128] 2. Experimental Results The test results are shown in Table 1.
[0129] Table 1. Relevant performance of batteries prepared in the examples and comparative examples.
[0130] As shown in Table 1, the present invention, by designing a first active material layer and a second active material layer with specific functions on the positive electrode sheet, helps to build a good conductive network, alleviates material loss and cracking at the R-corner, and is helpful for fast charging capacity retention and long cycle life. For details, please refer to the performance data of Examples 1-10.
[0131] The conventional lithium iron phosphate single-layer active material layer cathode used in Comparative Example 1, which lacks the first and second active material layers designed with specific functional materials in this invention, has poor electrode flexibility and conductivity, and no self-repairing performance, ultimately resulting in a significant decrease in the battery's 3C capacity retention rate and 1000-cycle capacity retention rate.
[0132] In Comparative Example 2, the first active material layer lacks elastic polymer, resulting in insufficient electrode flexibility and easy material shedding during cycling. This leads to a significant decrease in the battery's 3C capacity retention rate and 1000-cycle capacity retention rate, especially in the long-cycle (1000-cycle capacity retention rate), where the deterioration is even more pronounced.
[0133] Comparative Example 3 shows that the first active material layer lacks copper nanoparticles, resulting in insufficient conductivity and reduced fast charging performance.
[0134] In Comparative Example 4, the second active material layer lacked functional molecules, which resulted in the inability to repair cracks generated during cycling in a timely manner, leading to continuous deterioration over long cycles.
[0135] Comparative Example 5 lacks a first active material layer, resulting in insufficient conductivity of the positive electrode and low capacity retention under fast charging.
[0136] Comparative Example 6 lacks a self-healing layer (second active material layer), resulting in the inability to repair cracks in a timely manner during cycling, leading to poor long-term cycling performance.
[0137] Furthermore, comparing Examples 1-3, with thickness ratios of the first active material layer and the second active material layer of 1:1, 1:2, and 2:1 respectively, it can be found that when the thickness ratio of the first active material layer to the second active material layer is 1:1, the battery exhibits the best 3C capacity retention rate and 1000-cycle capacity retention rate. This indicates that when the upper self-healing layer (second active material layer) is too thick, the lower conductive network layer and elastic layer (first active material layer) are less, resulting in slightly poor overall conductivity of the electrode, insufficient kinetics under high 3C current, and a low 3C retention rate. Conversely, when the lower conductive network layer and elastic layer are too thick, the upper self-healing layer becomes thinner, leading to insufficient self-healing ability of electrode cracks in the later stages of cycling and a lack of long-cycle capacity retention.
[0138] Observing Examples 1 and 4, it can be found that when the functional molecule is adjusted to (EtO)3Si-(CH2)3-O-Zr(OEt)3, the prepared positive electrode also has good conductivity, flexibility and self-repair performance. Therefore, the 3C capacity retention rate and 1000-cycle capacity retention rate of the battery are also better.
[0139] Comparing Example 1 and Example 5, Example 5 uses amorphous carbon-coated copper nanoparticles, which slightly reduces conductivity and slightly reduces fast charging.
[0140] Comparing Example 1 and Example 6, Example 6 used polystyrene sulfonate (PSS) alone as the conductive polymer, which resulted in a decrease in battery performance.
[0141] Comparing Example 1 with Examples 7, 8, 9, and 10, the formulations of the first or second positive electrode slurry in Examples 7-10 have changed to some extent, which shows that the performance of the battery also fluctuates to some extent, indicating that the changes in the formulation have a certain impact on the performance of the battery.
[0142] Furthermore, the electron microscope images of the negative electrode (R-corner) disassembled after 1000 cycles of the battery in Example 3 and Comparative Example 1 show that there is no obvious lithium plating at the R-corner of the negative electrode corresponding to the positive electrode in Example 3, while lithium plating occurs at the R-corner of the negative electrode in Comparative Example 1 after cycling. This indicates that the positive electrode prepared by the present invention is more conducive to improving the problem of lithium plating at the R-corner of the negative electrode.
[0143] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention, but such modifications or substitutions are all within the scope of protection of the present invention.
Claims
1. A positive electrode plate, characterized in that: The positive electrode sheet comprises a current collector, a first active material layer, and a second active material layer in sequence, wherein the first active material layer and the second active material layer are arranged in sequence away from the current collector. The first active material layer includes a first active material, an elastic conductive polymer, and carbon-coated copper nanoparticles; The second active material layer includes a second active material and functional molecules; The functional molecule is an amphiphilic organic-inorganic hybrid molecule with the general formula R1-Spacer-M(OR2). n ; R1 includes at least one of phosphonic acid group (-PO(OH)2) and alkoxysilane group; Spacer is a flexible organic segment, including -(CH2CH2O). a -、-(CH2) b - at least one of the following, a = 1~6, b = 3~12; M(OR2) n In this context, M includes Al. 3+ Zr 4+ Ti 4+ Si 4+ Ce 4+ Y 3+ Mg 2+ At least one of them, R2 is an alkyl chain, and the alkyl chain has 2 to 4 carbon atoms and n is 2 to 5.
2. The positive electrode sheet as described in claim 1, characterized in that: The elastic conductive polymer includes at least one of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate complex and polystyrene sulfonate. And / or, the carbon-coated copper nanoparticles include at least one of graphene-coated copper nanoparticles and amorphous carbon-coated copper nanoparticles.
3. The positive electrode sheet as described in claim 1, characterized in that: The functional molecules include at least one of (HO)2OP-(CH2)3-O-Al(OC2H5)2 and (EtO)3Si-(CH2)3-O-Zr(OEt)3.
4. The positive electrode sheet as described in claim 1, characterized in that: Based on the total mass of the first active material layer, the content of the first active material is 60-70%, the content of the elastic conductive polymer is 22-32%, and the content of the carbon-coated copper nanoparticles is 3-8%. And / or, based on the total mass of the second active material layer, the content of the second active material is 92-98%, and the content of the functional molecule is 0.5-4%.
5. The positive electrode sheet as described in claim 1, characterized in that: The compaction density of the positive electrode sheet is 2.5-2.8 g / cm³. 3 ; And / or, the thickness ratio of the first active material layer to the second active material layer is 1~2:1~2.
6. The positive electrode sheet as described in claim 5, characterized in that: The thickness of the first active material layer is 80-180 μm; and / or, the thickness of the second active material layer is 80-180 μm.
7. The positive electrode sheet as described in claim 1, characterized in that: In the first active material layer, the first active material includes at least one of lithium iron phosphate cathode material, ternary nickel cobalt manganese cathode material, and lithium manganese iron phosphate cathode material; And / or, in the second active material layer, the second active material includes at least one of lithium iron phosphate cathode material, ternary nickel cobalt manganese cathode material, and lithium manganese iron phosphate cathode material.
8. The positive electrode sheet as described in claim 1, characterized in that: The first active material layer further includes a first dispersant and a first binder; based on the total mass of the first active material layer, the content of the first dispersant is 0.5~0.6%, and the content of the first binder is 0.4~2.5%. And / or, the second active material layer further includes a second dispersant, a second binder, and a conductive agent. Based on the total mass of the second active material layer, the content of the second dispersant is 0.2-0.3%, the content of the second binder is 0.7-3.3%, and the content of the conductive agent is 1.5-2%.
9. The positive electrode sheet as described in claim 8, characterized in that: The first dispersant includes at least one of polypropylene glycol phosphate, sodium dodecyl sulfate, polyethylene glycol, sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, polyacrylonitrile, and polyvinylpyrrolidone; And / or, the first adhesive comprises polyvinylidene fluoride; And / or, the second dispersant comprises at least one of polypropylene glycol phosphate, sodium dodecyl sulfate, polyethylene glycol, sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, polyacrylonitrile, and polyvinylpyrrolidone; And / or, the second adhesive comprises polyvinylidene fluoride; And / or, the conductive agent includes at least one of conductive carbon black, Ketjen black, carbon nanotubes, and graphene.
10. A battery, characterized in that: Including the positive electrode sheet as described in any one of claims 1 to 9.